Cognitive grammar a basic introduction - Langacker, Ronald W. (Oxford : Oxford University Press, 2008)
This introductory text draws together and refines the descriptive and theoretical aspects of cognitive grammar. In a unified manner, it accomodates both the conceptual and the social-interactive basis of linguistic structure, as well as the need for both functional explanation and explicit structural description.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Cognitive grammar